2012
DOI: 10.1186/1471-2105-13-s16-s6
|View full text |Cite
|
Sign up to set email alerts
|

Statistical protein quantification and significance analysis in label-free LC-MS experiments with complex designs

Abstract: BackgroundLiquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) is widely used for quantitative proteomic investigations. The typical output of such studies is a list of identified and quantified peptides. The biological and clinical interest is, however, usually focused on quantitative conclusions at the protein level. Furthermore, many investigations ask complex biological questions by studying multiple interrelated experimental conditions. Therefore, there is a need in the field for generic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
108
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 40 publications
0
108
0
Order By: Relevance
“…To identify proteins most significantly affected by the stimulus and to address the challenges posed by missing values, we used linear mixed-effects modeling (LiME). LiME, an improvement over ad hoc cutoffs or simple feature averaging, takes advantage of inherent replicate structure of the data and leverages information from a series of biological conditions to identify the significantly affected proteins (26,27). For PRKDC, LiME analysis revealed a systematic increase in peak area for the [s/t]Q containing phosphoPSMs, with >100-fold increase (P < 0.001) between combo and control treatments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify proteins most significantly affected by the stimulus and to address the challenges posed by missing values, we used linear mixed-effects modeling (LiME). LiME, an improvement over ad hoc cutoffs or simple feature averaging, takes advantage of inherent replicate structure of the data and leverages information from a series of biological conditions to identify the significantly affected proteins (26,27). For PRKDC, LiME analysis revealed a systematic increase in peak area for the [s/t]Q containing phosphoPSMs, with >100-fold increase (P < 0.001) between combo and control treatments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For MS studies, phosphopeptides were captured using [s/t]Q phosphomotif antibodies using PTMscan protocols (Cell Signaling Technology) (14) and were analyzed on an Orbitrap XL or Orbitrap-Velos. Database searches were performed using Mascot, peak areas determined using VistaQuant (25), and protein-level effects were assessed using LiME analysis (27). A detailed overview of the methods used here is presented in SI Materials and Methods and in Datasets S1-S3.…”
Section: Methodsmentioning
confidence: 99%
“…An unfortunate consequence of such a miss is that sometimes MS/MS-inferred peptides with vastly deviating abundances in run-torun or sample-to-sample comparisons are attributed to the same protein. These deviating peptides with questionable identities can drastically worsen the variances of protein abundances in the whole dataset and thus reduce the statistical power of the experiment (31). In contrast, in a quantification-centered approach, peptide abundance is the central factor to be investigated (9,15,(32)(33)(34).…”
mentioning
confidence: 99%
“…8 However, the efficiency of statistical comparison between metrics associated to a biological entity is questioned in the literature. [9][10][11][12] Indeed, such studies suffer from the high variance inherently found in biological systems, 9 from the low number of replicates typically analyzed, 10 and from experimental artifacts, errors and missing values. [13][14][15] As a result, the fine nuances of the proteomic variations are often not statistically significant when compared to the global variance of the system.…”
Section: Introductionmentioning
confidence: 99%